Chest computed tomography findings of 1271 patients with COVID-19 pneumonia and classifications with different age groups: a descriptive study from Istanbul, Turkey - Bulut,Safiye Sanem Dereli (2021)
SUMMARY OBJECTIVE: The objectives of this study were to describe lung computed tomography findings of patients with COVID-19 diagnosed by real-time reverse transcription polymerase chain reaction test, investigate whether the findings differ regarding age and gender, and evaluate the diagnostic performance of chest computed tomography based on the duration of symptoms at the time of presentation to the hospital. METHODS: From March 11 to May 11, 2020, 1271 consecutive patients (733 males and 538 females) were included in this retrospective, cross-sectional study. Based on age, patients were divided into five separate subgroups. Then based on the duration of symptoms, patients were divided into five separate phases. The presence of lung lesion(s) and their characteristics, distribution patterns, and the presence of concomitant pleural thickening/effusion and other findings (malignancy, metastasis, chronic obstructive pulmonary disease, interstitial lung disease, bronchiectasis, bronchiectasis, cardiomegaly, pericardial effusion) were evaluated by five radiologists independently. RESULTS: The “normal lung computed tomography finding” was the most common chest CT finding (37%), followed by ground-glass opacity (31%). Regardless of the shape of the lesion, the distribution features were significant (peripheral, subpleural, and lower lobe distribution) (p<0.05). The presence of pleural thickening posteriorly and adjacent to the lesion was statistically different in groups 1–3 (p<0.05). Other concomitant pathologies, except pulmonary congestion, did not suppress the typical findings of COVID-19. CONCLUSION: Chest computed tomography findings were mostly normal in the early phase (P1). Therefore, it may be appropriate to perform the first computed tomography screening of COVID-19 after 6 days to decrease the radiation exposure.